Synthesis of Fe3O4-Reduced Graphene Oxide Modified Tissue-Paper and Application in the Treatment of Methylene Blue - Thanh Huyen, Le; Sy Duc, Dao; Xuan Hoan, Nguyen; Huu Tho, Nguyen; Xuan Viet, Nguyen (VNU Journal of Science: Natural Sciences and Technology; Vol 35 No 3, 2019)
Graphene-based composites have received a great deal of attention in recent year because the presence of graphene can enhance the conductivity, strength of bulk materials and help create composites with superior qualities. Moreover, the incorporation of metal oxide nanoparticles such as Fe 3 O 4 can improve the catalytic efficiency of composite material. In this work, we have synthesized a composite material with the combination of reduced graphene oxide (rGO), and Fe 3 O 4 modified tissue-paper (mGO-PP) via a simple hydrothermal method, which improved the removal efficiency of the of methylene blue (MB) in water. MB blue is used as the model of contaminant to evaluate the catalytic efficiency of synthesized material by using a Fenton-like reaction. The obtained materials were characterized by SEM, XRD. The removal of materials with methylene blue is investigated by UV-VIS spectroscopy, and the result shows that mGO-PP composite is the potential composite for the color removed which has the removal efficiency reaching 65% in acetate buffer pH = 3 with the optimal time is 7 h. Keywords Graphene-based composite, methylene blue, Fenton-like reaction. References [1] Ma Joshi, Rue Bansal, Reng Purwar, Colour removal from textile effluents, Indian Journal of Fibre & Textile Research, 29 (2004) 239-259 http://nopr.niscair.res.in/handle/123456789/24631. [2] Kannan Nagar, Sundaram Mariappan, Kinetics and mechanism of removal of methylene blue by adsorption on various carbons-a comparative study, Dyes and pigments, 51 (2001) 25-40 https://doi.org/10.1016/S0143-7208(01)00056-0. [3] K Rastogi, J. N Sahu, B. C Meikap, M. N Biswas, Removal of methylene blue from wastewater using fly ash as an adsorbent by hydrocyclone, Journal of hazardous materials, 158 (2008) 531-540.https://doi.org/10.1016/j.jhazmat.2008.01. 105. [4] Qin Qingdong, Ma Jun, Liu Ke, Adsorption of anionic dyes on ammonium-functionalized MCM-41, Journal of Hazardous Materials, 162 (2009) 133-139 https://doi.org/10.1016/j.jhazmat. 2008.05.016. [5] Mui Muruganandham, Rps Suri, Sh Jafari, Mao Sillanpää, Lee Gang-Juan, Jaj Wu, Muo Swaminathan, Recent developments in homogeneous advanced oxidation processes for water and wastewater treatment, International Journal of Photoenergy, 2014 (2014). http://dx. doi.org/10.1155/2014/821674. [6] Herney Ramirez, Vicente Miguel , Madeira Luis Heterogeneous photo-Fenton oxidation with pillared clay-based catalysts for wastewater treatment: a review, Applied Catalysis B: Environmental, 98 (2010) 10-26 https://doi.org/ 10.1016/j.apcatb.2010.05.004. [7] Guo Rong, Jiao Tifeng, Li Ruifei, Chen Yan, Guo Wanchun, Zhang Lexin, Zhou Jingxin, Zhang Qingrui, Peng Qiuming, Sandwiched Fe3O4/carboxylate graphene oxide nanostructures constructed by layer-by-layer assembly for highly efficient and magnetically recyclable dye removal, ACS Sustainable Chemistry & Engineering, 6 (2017) 1279-1288 https://doi.org/10.1021/acssuschemeng.7b03635. [8] Sun Chao, Yang Sheng-Tao, Gao Zhenjie, Yang Shengnan, Yilihamu Ailimire, Ma Qiang, Zhao Ru-Song, Xue Fumin, Fe3O4/TiO2/reduced graphene oxide composites as highly efficient Fenton-like catalyst for the decoloration of methylene blue, Materials Chemistry and Physics, 223 (2019) 751-757 https://doi.org/ 10.1016/j.matchemphys.2018.11.056. [9] Guo Hui, Ma Xinfeng, Wang Chubei, Zhou Jianwei, Huang Jianxin, Wang Zijin, Sulfhydryl-Functionalized Reduced Graphene Oxide and Adsorption of Methylene Blue, Environmental Engineering Science, 36 (2019) 81-89 https://doi. org/10.1089/ees.2018.0157. [10] Zhao Lianqin, Yang Sheng-Tao, Feng Shicheng, Ma Qiang, Peng Xiaoling, Wu Deyi, Preparation and application of carboxylated graphene oxide sponge in dye removal, International journal of environmental research and public health, 14 (2017) 1301 https://doi.org/10.3390/ijerph14111301. [11] Yu Dandan, Wang Hua, Yang Jie, Niu Zhiqiang, Lu Huiting, Yang Yun, Cheng Liwei, Guo Lin, Dye wastewater cleanup by graphene composite paper for tailorable supercapacitors, ACS applied materials & interfaces, 9 (2017) 21298-21306 https://doi.org/10.1021/acsami.7b05318. [12] Wang Hou, Yuan Xingzhong, Wu Yan, Huang Huajun, Peng Xin, Zeng Guangming, Zhong Hua, Liang Jie, Ren MiaoMiao, Graphene-based materials: fabrication, characterization and application for the decontamination of wastewater and wastegas and hydrogen storage/generation, Advances in Colloid and Interface Science, 195 (2013) 19-40 https://doi. org/10.1016/j.cis.2013.03.009. [13] Marcano Daniela C, Kosynkin Dmitry V, Berlin Jacob M, Sinitskii Alexander, Sun Zhengzong, Slesarev Alexander, Alemany Lawrence B, Lu Wei, Tour James M, Improved synthesis of graphene oxide, ACS nano, 4 (2010) 4806-4814 https://doi.org/10.1021/nn1006368. [14] Zhang Jiali, Yang Haijun, Shen Guangxia, Cheng Ping, Zhang Jingyan, Guo Shouwu, Reduction of graphene oxide via L-ascorbic acid, Chemical Communications, 46 (2010) 1112-1114 http://doi. org/10.1039/B917705A [15] Gong Ming, Zhou Wu, Tsai Mon-Che, Zhou Jigang, Guan Mingyun, Lin Meng-Chang, Zhang Bo, Hu Yongfeng, Wang Di-Yan, Yang Jiang, Nanoscale nickel oxide/nickel heterostructures for active hydrogen evolution electrocatalysis, Nature communications, 5 (2014) 4695 https:// doi.org/10.1038/ncomms5695. [16] Wu Zhong-Shuai, Yang Shubin, Sun Yi, Parvez Khaled, Feng Xinliang, Müllen Klaus, 3D nitrogen-doped graphene aerogel-supported Fe3O4 nanoparticles as efficient electrocatalysts for the oxygen reduction reaction, Journal of the American Chemical Society, 134 (2012) 9082-9085 https://doi.org/10.1021/ja3030565. [17] Nguyen Son Truong, Nguyen Hoa Tien, Rinaldi Ali, Nguyen Nam Van, Fan Zeng, Duong Hai Minh, Morphology control and thermal stability of binderless-graphene aerogels from graphite for energy storage applications, Colloids and Surfaces A: Physicochemical and Engineering Aspects, 414 (2012) 352-358 https://doi.org/ 10.1016/j.colsurfa.2012.08.048. [18] Deng Yang, Englehardt James D, Treatment of landfill leachate by the Fenton process, Water research, 40 (2006) 3683-3694 https://doi.org/ 10.1016/j.watres.2006.08.009.